Entrepreneurial Decision-Making: The Role of e-Commerce and Accounting Information Systems - Muhamad Rizky Wijaya; Jumiran Jumiran; Yulis Nuryanti; Gusli Chidir; Didi Sutardi (Edumaspul: Jurnal Pendidikan, 2022)
This study aims to obtain evidence regarding the influence of e-commerce on decision-making for entrepreneurship, and the effect of using accounting information systems on decision-making for entrepreneurship. This research was conducted at one of the universities in Jakarta. The data collection method used in this study was a survey method with a questionnaire technique. The population in this study were students of all majors who had status as active students. The data used in this study is primary data obtained by distributing questionnaires directly to 102 respondents using a purposive sampling technique. The data analysis used is multiple linear regression analysis. The results of the analysis show that e-commerce has a positive effect on decision-making for entrepreneurship, and the use of accounting information systems has a positive effect on decision-making for entrepreneurship.